Measurement model for national logistics cost of Indonesia - Saragih, Nova Indah; Turnip, Peri (Journal Industrial Servicess, 2024)
National logistics costs are a crucial indicator for nations to monitor and evaluate the efficiency of their logistics activities. They also serve as an essential foundation for economic growth. A lack of data is the primary challenge in measuring national logistics costs. To accurately assess these costs, countries must have reliable statistics on transportation and inventory. Without such data, estimating logistics costs becomes highly challenging, and the results are often unreliable. This research aims to develop a national logistics cost model for Indonesia. The key contribution of this study is that it represents the first effort to create a logistics cost model specifically for Indonesia. The model is developed based on the frameworks used in the United States of America, the Republic of Korea, and South Africa, adjusted to fit the data available in Indonesia. It comprises three main components: transportation costs, inventory handling costs, and administrative costs. Transportation and inventory handling costs are modeled based on the approach used in the Republic of Korea, while administrative costs are based on the model from the United States of America. This study introduces 25 calculation scenarios, and based on the selected scenario, the average national logistics cost of Indonesia from 2004 to 2010 is found to be 27.94% of GDP.